2014
DOI: 10.1111/dote.12164
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical features in patients with eosinophilic esophagitis living in an urban and rural environment

Abstract: Eosinophilic esophagitis (EoE) has been associated with exposure to aeroallergens. Living in different locations (urban vs. rural) could potentially expose individuals to different environmental factors. Currently, there is limited data on the matter, and all was based on small population studies that did not exclude proton pump inhibitor (PPI)-responsive esophageal eosinophilia in their cohort. The primary aim of this study was to determine the prevalence of EoE in an urban versus rural population and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Our population had similar clinical characteristics as reported in other regions, including a high rate of atopy and allergen sensitization, suggesting that patients may present similarly regardless of geographic location. 17,19,2224 There were also no differences found between patients living in rural vs nonrural counties. The most common clinical symptoms included vomiting, abdominal pain, and heart-burn, with older patients having a higher incidence of dysphagia and food impaction.…”
Section: Discussionmentioning
confidence: 83%
“…Our population had similar clinical characteristics as reported in other regions, including a high rate of atopy and allergen sensitization, suggesting that patients may present similarly regardless of geographic location. 17,19,2224 There were also no differences found between patients living in rural vs nonrural counties. The most common clinical symptoms included vomiting, abdominal pain, and heart-burn, with older patients having a higher incidence of dysphagia and food impaction.…”
Section: Discussionmentioning
confidence: 83%
“…With the exception of one prior physician survey which found that cases of EoE were more common in some rural areas (6), a recent study detecting no difference in the frequency of EoE diagnosis in urban or rural settings using a 1,000 person/square mile cut-point for rural versus urban status (30), and an abstract from a single center showing more EoE cases from rural areas than urban areas (23), this association has not been previously described in the EoE literature. In some respects, this finding is counterintuitive.…”
Section: Discussionmentioning
confidence: 99%
“…The second was a retrospective cohort that compared clinical features of EoE in urban and rural regions, based on 2010 US census data, using a population density cut off of 1000 people / square mile. 46 There was no statistically significant difference in prevalence between urban and rural areas, but some differences in clinical features. Urban patients, for example, were more likely to present with dysphagia, while rural patients were more likely to complain of heartburn and reflux.…”
Section: Resultsmentioning
confidence: 80%
“…A similar statement could be made for EoE being more common in areas with low population density. 36,37,46 This broad finding currently lacks a definitive explanation, and while multiple hypotheses are possible, further research is needed to explicate the underlying reasons for this trend. The studies on early life exposures, while intriguing and more granular, are still preliminary.…”
Section: Discussionmentioning
confidence: 99%